A Qualitative Study on the Point System: An Integration Strategy between Student Affairs Management and the School Discipline Enforcement Team (PDS) in Fostering Student Discipline Compliance - Wahyu Putri Kinanti; Nurul Latifatul Inayati (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study aims to analyze the integration strategy between Student Affairs Management and the School Discipline Enforcement Team (PDS) through a point system in fostering student discipline compliance at SMA Negeri 1 Sragen and to identify implementation challenges. The study employed a qualitative approach with field research and a phenomenological perspective. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The results indicate that the integration is implemented through the POAC framework with a transparent and systematic point system applied through programs such as morning greetings and sudden inspections. The system functions not only as a disciplinary control mechanism but also as an educational and humanistic character-building strategy. Challenges include limited supervision time, differing perceptions among educators, and students’ family backgrounds. Therefore, strengthening coordination and parental involvement is essential.